Criminal Investigation of Motorcycle Stealing Goods - Yusril Ilza Amri; Bambang Tri Bawono; Ira Alia Maerani (Law Development Journal, 2021)
This study aims to identify and analyze the factors that cause the increase in the number of criminal acts of arresting the results of motorcycle theft in the jurisdiction system of the Pati Regency Resort, as well as to identify and analyze the investigative actions carried out by the Pati Regency Police in the conception of law enforcement. This study uses a juridical empirical (sociological) approach. The results showed that there was an increase in criminal acts of detention of the results of motor vehicle theft in the jurisdiction of the Pati Police, including the desire to own a motorized vehicle, the economic condition of the perpetrator, the perpetrator's friendship, low legal knowledge, the intention to help the perpetrator of theft, persuade and lure profits, and in cooperation with many parties. Then the investigation carried out by the Pati Police on the criminal act of arresting a motor vehicle resulting from theft through 4 (four) stages, including: receipt of reports, summons, confiscation, and investigation. The obstacles faced by the Pati Resort Police included: the perpetrator moved from place to place, the perpetrator lost evidence, the lack of public participation, and the difficulty of proving it. Efforts made by the Pati Resort Police include 3 (three) attempts. Pre-emptive efforts are carried out by providing legal counseling to the public regarding criminal acts of theft and detention. Preventive measures are carried out by conducting raids and patrolling locations deemed prone to theft. The last resort.